Spectrum of Kidney Pathology in Patients With Syphilis - Diana Fang; Aaron J. Storey; Samar I. Hassen; Christopher P. Larsen; Tiffany N. Caza (Kidney International Reports)
Introduction: Syphilis has been associated with multiple kidney diseases, primarily studied within small series. A large cohort of patients with active syphilis who underwent kidney biopsy were examined to evaluate the histopathologic spectrum and clinicopathologic features of the disease. Methods: Patients with syphilis who underwent a native kidney biopsy were identified from renal pathology archives at Arkana Laboratories. Patients were identified through a clinical history of active syphilis in medical records and/or positive serologic testing (rapid plasma reagin, venereal disease research laboratory, or antitreponemal antibodies). Results: A total of 102 patients with syphilis who underwent kidney biopsy were identified. The mean age was 41.0 ± 14.0 years with male predominance (87.3%). The majority presented with acute kidney injury (AKI) with a mean creatinine of 4.7 ± 4.0 mg/dl. Coinfections, including HIV, hepatitis B virus, and hepatitis C virus were common. The most common disease states included membranous nephropathy (MN, n = 29), HIV-associated diseases (n = 21), acute interstitial nephritis (AIN, n = 10), acute tubular injury (ATI, n = 24), infection-associated glomerulonephritis (GN) (n = 8), and IgA nephropathy (n = 7). Of the patients with MN (28.4%), the majority were neuron-derived neurotropic factor (NDNF) positive and frequently demonstrated staining for multiple immune reactants, particularly C1q. Of the patients with HIV-associated pathology (20.6%), 81.0% had collapsing glomerulopathy and 33.3% had mesangial immune complex deposition (HIV-associated immune complex disease of the kidney [HIVICK]). Most patients with AIN (70%) demonstrated plasma cell–rich interstitial infiltrates. Conclusion: A spectrum of kidney pathology diagnoses is seen in patients with syphilis, with the majority of patients presenting with AKI. Coinfections, and pathology related to coinfections, were common.